Stability in the Pseudo-state Formalism of Discrete Systems Controlled in the Presence of Intermittent Sensor Faults - V. Dionísio, R. (2018)
Trabalho apresentado em IFAC Workshop on Adaptation and Learning in Control and Signal Processing, 26-28 de Agosto de 2010, Antalya, Turquia.